2022
DOI: 10.1111/ijet.12358
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in leisure—Effects on labor‐leisure choice

Abstract: This paper introduces the idea of a forward‐looking reference benchmark on both consumption and leisure in the context of a Ramsey–Cass–Koopmans growth model by assuming that in addition to consumption and leisure the household utility also depends on reference benchmarks of future anticipated consumption and leisure. We analyze the macrodynamic equilibrium, contrasting it to the case when the reference benchmarks are backward‐looking. We investigate if the presence of anticipation in leisure can lead to smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…See alsoChatterjee et al (2023) for an interesting example of a future anticipation benchmark applied to both consumption and leisure.15 It is often found that monetary-policy effects can have heterogeneous effects across firms and households, and across different stages of the economic cycle, see inter alia,Ferrando et al (2023).344 | FARIA McADAM…”
mentioning
confidence: 99%
“…See alsoChatterjee et al (2023) for an interesting example of a future anticipation benchmark applied to both consumption and leisure.15 It is often found that monetary-policy effects can have heterogeneous effects across firms and households, and across different stages of the economic cycle, see inter alia,Ferrando et al (2023).344 | FARIA McADAM…”
mentioning
confidence: 99%